Preparation and Characterization of Nanostructured Lipid Carriers Retinol Based on Patchouli Oil (Pogostemon cablin Benth.): Characteristic Test and Release Profile - Angga Saputra Yasir; Veni Putri Nurhayati; Aida Febina Sholeha; Okta Amelia (Jurnal Kimia Sains dan Aplikasi, 2026)
Nanostructured Lipid Carriers (NLC) were developed as a topical delivery system to overcome the limitations of retinol, such as low stability and uncontrolled release. This study used patchouli oil (PO) as a liquid lipid component to enhance the efficiency of retinol encapsulation and lipid matrix stability. The purpose of this study was to create, characterize, and test the release profile and in vitro antioxidant activity of the NLC retinol-patchouli oil (NLC-RPO) system. Optimization was performed by determining the ratio of solid lipid to liquid lipid, and the formulation was prepared using the high-shear homogenization and rapid cooling (ice bath) method. Characterizations carried out included particle size, PDI, zeta potential (ZP), morphology, entrapment efficiency (EE), FTIR, physical stability, pH, and viscosity. The release profile was tested using a Franz diffusion cell. The optimal NLC-RPO formula (1.2% cetyl alcohol, 0.8% patchouli oil, 0.3% retinol, 1% span 60, 4% tween 80) was successfully obtained and demonstrated suitable characteristics: particle size of 114.4 ± 0.42 nm, PDI 0.29 ± 0.02, ZP -32 ± 1.58 mV, EE 86.56 ± 4.24 % (n=3), and spherical morphology. The physicochemical evaluation revealed a pH of 5.59, pseudoplastic flow behavior, and good physical stability as confirmed by centrifugation testing. The NLC-RPO formulation demonstrated a modestly slower in vitro release rate at earlier time points vs free retinol under our test conditions. The antioxidant activity, tested using the DPPH method, showed that NLC-RPO had stronger antioxidant activity, with an IC50 of 99.59 ± 0.49 (n=3), compared to retinol and PO. Further research could conduct retinol degradation tests and in vivo penetration tests to comprehensively validate dermatological efficacy or to develop it into an anti-aging cosmetic.